At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
Y= -4 :)
Steps:
Apply rule
-y + 3 = 7
Subtract 3 from both sides
-y + 3 - 3 = 7 - 3
Simplify
-y = 4
Divide both sides by -1
-y/-1 = 4/-1
Simplify
y = -4
Y= -4 :)
Steps:
Apply rule
-y + 3 = 7
Subtract 3 from both sides
-y + 3 - 3 = 7 - 3
Simplify
-y = 4
Divide both sides by -1
-y/-1 = 4/-1
Simplify
y = -4
Hey there!
-y - (-3) = 7
-y + 3 = 7
-y = 7 - 3
-y = 4
=> y = -4
Hope it helps ya!
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.